THE PHENOMENON OF ONLINE GAME ADDICTION ON CHILDREN'S MORAL BEHAVIOR: ITS IMPACT AND PREVENTION - Kusuma Agdhi Rahwana; Ma’adul Yaqien Makkarateng; Murthada; Nunung Suryana Jamin; Dedah Ningrum (International Journal of Teaching and Learning, 2024)
The increasingly rapid development of information and communication technology has had a significant impact on social life. Even though it provides many potential benefits from the internet, it gives rise to problematic behavior, including online games where the majority of users are students. However, little is known about the impact of online games on group behavior and norms in online interactions. Even though online games are useful for self-relaxation, their negative impact makes individuals lose track of time so that they forget their daily tasks and obligations such as studying, going to school, helping parents, socializing with many people, and also carrying out spiritual activities such as worship. The positive impacts of online games are training children in cooperation, being able to learn English, training concentration, speed, creativity, fun, and reducing stress. Behind this positive impact there is a dangerous threat from online games, namely children become lazy, addicted, and there is decadence or moral decline. For this reason, online games as a form of technological development need to be addressed wisely so that they do not have a negative impact on teenagers. Thus, teenagers need to be given efforts to prevent online game addiction, one of which is limiting playing online games, implementing healthy routines, carrying out cognitive behavioral therapy, and professional help so that they can hopefully avoid online game addiction.